Strategies for the dynamization of sustainable business ecosystems—a view from Medellin’s SMEs - Ochoa, Santiago Cadavid; Serna, Luis Miguel Gomez; Sossa, Jhon Wilder Zartha; Mendoza, Gina Lía Orozco (Frontiers in Sustainable Cities, 2025)
A confluence of internal and external factors has contributed to a growing optimism regarding the viability of sustainability positions, evidenced by a proliferation of studies on this topic at the global level. We integrate this comprehension with the pivotal function that SMEs perform within the business network of the city of Medellín and examine the extent of their engagement with sustainability issues. This study examines the obstacles that small and medium-sized enterprises (SMEs) encounter globally and contrasts them with the incentives that various actors, including government agencies and private entities, implement to address these types of obstacles. A search of SCOPUS using the equation and the definition of the keyword “sustainability,” along with the terms “barriers,” “incorporation,” “entrepreneurship,” “creation,” and “SME,” yielded 107 articles. The 50 most cited articles related to the research topic were selected; however, seven of them were found to be irrelevant to the research topic and were thus excluded. Consequently, 43 articles were subjected to analysis for the purposes of this study. The focus of this study is centered on Colombia, specifically in the city of Medellin, the capital of the Antioquia department. For this purpose, we have standardized both the barriers and incentives reviewed, resulting in 18 barriers and 13 incentives. The AHP model was employed to ascertain the level of importance of each barrier, group them into six categories, and evaluate and compare the incentives in terms of their efficacy in addressing these barriers. Based on these findings, strategies are proposed to enhance the company’s market position and competitive advantage, thereby fostering a more robust business network in the city.